Formulation optimization and synergistic effects of flocculation–solidification–vacuum preloading on sludge treatment - Lufan Li; Hongen Wu; Xukun Yang; Jianwen Wei; Yunliang Cui (Scientific Reports)
Abstract Rapid infrastructure development generates large volumes of high-water-content sludge, creating an urgent need for efficient recycling and management strategies. This study introduces the flocculation–solidification–vacuum preloading (FSVP) method to enhance dewatering efficiency and strength development, facilitating subsequent mechanical construction requirements. To enhance solidification and reduce cement consumption, the response surface method was used to determine the optimal composite curing agent, which consists of 53% cement, 32% rice husk ash, and 15% sodium silicate. Vacuum dewatering was applied to sludge samples treated with different flocculants and curing agents to assess their synergistic effects on soil improvement. The mixed flocculant of polyaluminum chloride and anionic polyacrylamide significantly increased the micropore content and compactness, with pore sizes primarily concentrated around 0.01 μm. While the flocculant facilitated efficient drainage, required unconfined compressive strength could only be achieved with the further addition of a curing agent. The optimal composite curing agent formulation induced hydration and pozzolanic reactions, filling larger pores with cementitious materials and enhancing soil strength. As a result, the vane shear strength reached 58 kPa and unconfined compressive strength reached 365 kPa at 7 days, further increasing to 586 kPa at 28 days.